9x(y+4)-10(y+4)
(9x-10)(y+4)
<span>In the function "y=x2-18x" the goal is to find the value of the letter x. We know that y equals x2-18x. First, recognize that x2 is the same thing as 2x. So changing the problem to "y=2x-18x". We can subtract 18x from 2x, which leaves us with -16x. Now the problem looks like this: y=-16x. In order to get x by itself, we will need to do the same thing to both sides of the equation. In this case, we want the answer to be x by itself, or (1x) which is the same thing. We divide both sides of the equation by (-16). We are left with the following: y/-16=x. Basically, in words, x equals y divided by negative 16.</span>
<h2><u>Part A:</u></h2>
Let's denote no of seats in first row with r1 , second row with r2.....and so on.
r1=5
Since next row will have 10 additional row each time when we move to next row,
So,
r2=5+10=15
r3=15+10=25
<u>Using the terms r1,r2 and r3 , we can find explicit formula</u>
r1=5=5+0=5+0×10=5+(1-1)×10
r2=15=5+10=5+(2-1)×10
r3=25=5+20=5+(3-1)×10
<u>So for nth row,</u>
rn=5+(n-1)×10
Since 5=r1 and 10=common difference (d)
rn=r1+(n-1)d
Since 'a' is a convention term for 1st term,
<h3>
<u>⇒</u><u>rn=a+(n-1)d</u></h3>
which is an explicit formula to find no of seats in any given row.
<h2><u>Part B:</u></h2>
Using above explicit formula, we can calculate no of seats in 7th row,
r7=5+(7-1)×10
r7=5+(7-1)×10 =5+6×10
r7=5+(7-1)×10 =5+6×10 =65
which is the no of seats in 7th row.
Answer:
B
Step-by-step explanation:
31-23=8
41-31=10
53-41=12
So next number should be 53+14, that is 67.
Follow the rule:
67+16=83
83+18=101